Construção e validação de um instrumento imagético para avaliação da intensidade e localização de dor em adultos com plexobraquialgia - Celia Maria de Oliveira (2012)
Neck and shoulder traumas cause traction/ stretch which induces lesions on the brachial plexus, whose nervous structure is formed at C5, C6, C7, C8 and T1. Brachial plexus trauma causes dysfunction by neurologic lesion and by pain on the affected limb. This pain persists and brings physical and psychological suffering and interferes in the persons social and economic daily life. Current accessible tools to assess pain do not serve to the specificity of brachialgy to allow a more accurate assessment, i.e., the pain extent in the path of the plexus. Therefore, there was a need for creating and validating an imaging tool to assess pain in adults with brachial plexopathy, which can provide a fast and easy implementation and allow to distinguish the pains intensity, site and extent in the plexus path. This study was accomplished in phases: creation of a scale with colors among a general population (n=405) to measure pain intensity; presenting the following results: yellow to indicate light pain, orange for mild pain, red for strong pain, and black for unbearable pain. Creation and clinical validation of an imaging tool to locate and measure the pain intensity in patients with brachial plexopathy. Participants demographic and epidemiological profile was identified. The majority was composed by young adults, male, who had less than 11 years of education, who was engaged in manual labors, and who suffered a motorcycle accident. The scale with colors was validated and rendered an agreement of 98.9% among the patients. To validate pain site on the body diagram, the tool was applied among 35 patients and surgery was chosen as an external criterion. Specificity index was high for each trunk and low when the lesion was present in all the trunks. Sensitivity was low for each trunk and high when the lesion was in all the trunks. Results of the study provide a scale with colors to measure pain intensity and an imaging tool to pinpoint and measure pain in patients with brachial plexopathy.